The T-cell Response to Epstein-Barr Virus–New Tricks From an Old Dog - Long, Heather M.; Meckiff, Benjamin J.; Taylor, Graham S. (Frontiers in Immunology, 2019)
Epstein-Barr virus (EBV) infects most people and establishes life-long infection controlled by the host’s immune system. The genetic stability of the virus, deep understanding of the viral antigens and immune epitopes recognised by the host’s T-cell system and the fact that recent infection can be identified by the development of symptomatic infectious mononucleosis makes EBV a powerful system in which to study human immunology. The association between EBV and multiple cancers also means that the lessons learned have strong translational potential. Increasing evidence of a role for resident memory T-cells and non-conventional gamma/delta T-cells in controlling EBV infection suggests new opportunities for research and means the virus will continue to provide exciting new insights into human biology and immunology into the future.